The lack of association between PADI4_94 or PADI4_104 polymorphisms and RF, ACPA and anti-PAD4 in patients with rheumatoid arthritis - Ciesla, Marek; Kolarz, Bogdan; Darmochwal-Kolarz, Dorota (Scientific reports, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that leads to chronic inflammation of synovial tissue, ultimately causing joint damage, disability, and premature mortality. The peptidylarginine deiminase (PAD) family of proteins is involved in the production of anticitrullinated peptide antibodies (ACPA), which are clinically relevant markers of RA. ACPA recognizes citrullinated proteins generated mainly by PAD4. Polymorphisms of the PADI4 gene have been associated with RA in Asian populations, but in Europeans these associations are still difficult to estimate. A total of 147 subjects, 122 patients with RA, 52 ± 12.3 aged, 84.4% women and 25 healthy controls, 53 ± 8.4 aged, 72% women were enrolled in the study. Two single nucleotide polymorphisms (SNPs) of the PADI4 gene ( PADI4_94 , rs2240340 and PADI4_104 , rs1748033) were genotyped using a real-time polymerase chain reaction. Genetic models (co-dominant-1 and 2, dominant, over-dominant, and recessive) were applied to find the associations between genotypes and ACPA as well as PAD4 antibodies (anti-PAD4) levels. We found no relationship between the distribution of genotypes in different genetic models and the levels of anti-PAD4, ACPA and RF antibodies. There were also no differences with respect to the haplotypes. Genetic variants PADI4_94 and PADI4_104 may not be clinically relevant as prognostic factors in patients with established RA.